How minutes tune the economy? - Gryčová, Marta; Hurník, Jaromír, 1975-; Sedláček, Petr; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2010)
Abstract Based on the Romer and Romer (1989) methodology this paper analyzes behavior of the US Federal Reserve System (FED) and the Czech National Bank (CNB) during the recent crisis. It explores minutes and press releases from the meetings of the Bank Board of the CNB and the Federal Open Market Committee of the FED, i.e. on one hand from the side of a small open economy that has been hit mainly through decline in foreign demand, on the other from the side of a big closed economy, in which the recent crisis has originated. It compares reaction in interest rate and adequacy of unconventional measures with a prediction of a simple 'Taylor rule' (Taylor, 1993) and tries to evaluate the adequacy of the overall reaction of mentioned central banks to the crisis.
Vedoucí práce: Jaromír Hurník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses